PERSEPSI MASYARAKAT SERTA PIHAK TERKAIT TERHADAP FUNGSI HUTAN KOTA ARWINAS DI KECAMATAN SIAK KABUPATEN SIAK - Anggun Tri Nande; Nurul Qomar; Yossi Oktorini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
Arwinas Urban Forests is a Green Open Space in Siak Regency with an area of 33.1 ha. Urban forests have a functions to improve, maintain the micro climate, aesthetic values, absorb water, balance the harmony of the city environment and preserve biodiversity. Communities and stakeholders are involved in urban forests management, but their participation was influenced by perceptions of the functions of urban forests. Perception affects a person's behavior towards the object and environment. This research purpose aperceptions of the community and stakeholders about the functions of the existence of the Arwinas Urban Forests. This research used quantitative and qualitative methods. Data is collected through interviews, observation and literature. Primary data were analyzed using chi-square test and ranks spearman correlation test with qualitative descriptive analysis. The results of the research revealed that the community and stakeholders had a positive perception, 52.3% of the community respondents and 94.4% of the other parties respondents stated that they agreed to the function of the Arwinas Urban Forests. Based on chi-square analysis, occupational factors and the level of education of the community and related parties have a real relationship with the perception of the functions of the Arwinas Urban Forests. The results of the rank spearman analysis showed the strength of the relationship between community perceptions of the function of the forest and occupational factors and the level of education are categorized as medium and strong. The results of the rank spearman analysis showed the strength of the relationship between the perceptions of parties related to urban forest functions with occupational factors and the level of education factors are strong. Keywords:Arwinas Urban Forest, Function,Perception.